Pseudoaneurysm of aortocoronary vein graft secondary to late venous rupture: case report and literature review. Issue 2 (August 1993) - Kallis, P; Keogh, B E; Davies, M J
Abstract : Formation of pseudoaneurysms of saphenous vein grafts after coronary artery bypass grafting has been reported previously in relation to anastomoses or secondary to infection. Pseudoaneurysm of the saphenous vein graft after late rupture of the saphenous vein and containment by the obliterated pericardial cavity has not been documented. Such a case is reported and published reports of similar cases are reviewed.